Salivary proteins of Phloeomyzus passerinii, a plant-manipulating aphid, and their impact on early gene responses of susceptible and resistant poplar genotypes. (May 2020) - Portillo Lemus, Luis; Tricard, Jessy; Duclercq, Jérôme; Coulette, Quentin; Giron, David; Hano, Christophe; Huguet, Elisabeth; Lamblin, Frédéric; Cherqui, Anas; Sallé, Aurélien
Highlights: Phloeomyzus passerinii secretes a diverse and peculiar repertoire of effectors. Salivary extracts prevented early responses of biotic stress-responsive host genes. These extracts altered auxin and cytokinin pathways in a susceptible host genotype. These pathways modifications could lead to an intracellular accumulation of auxin. This accumulation could interfere with biotic stress signaling and host metabolism. Abstract: Successful plant colonization by parasites requires the circumvention of host defenses, and sometimes a reprogramming of host metabolism, mediated by effector molecules delivered into the host. Using transcriptomic and enzymatic approaches, we characterized salivary glands and saliva of Phloeomyzus passerinii, an aphid exhibiting an atypical feeding strategy. Plant responses to salivary extracts of P. passerinii and Myzus persicae were assessed with poplar protoplasts of a susceptible and a resistant genotype, and in a heterologous Arabidopsis system. We predict that P. passerinii secretes a highly peculiar saliva containing effectors potentially interfering with host defenses, biotic stress signaling and plant metabolism, notably phosphatidylinositol phosphate kinases which seemed specific to P. passerinii . Gene expression profiles indicated that salivary extracts of M. persicae markedly affected host defenses and biotic stress signaling, while salivary extracts of P. passerinii induced only weak responses. The effector-triggered susceptibility was characterized by downregulations of genes involved in cytokinin signaling and auxin homeostasis. This suggests that P. passerinii induces an intracellular accumulation of auxin in susceptible host genotypes, which is supported by histochemical assays in Arabidopsis . This might in turn affect biotic stress signaling and contribute to host tissue manipulation by the aphid.